miR-137: a potential therapeutic target for lung cancer - Liu, Shuanshuan; Ruan, Yanyun; Chen, Xu; He, Bao; Chen, Qi (Frontiers in Cell and Developmental Biology, 2024)
Lung cancer is a prevalent malignancy and the leading cause of cancer-related deaths, posing a significant threat to human health. Despite advancements in treatment, the prognosis for lung cancer patients remains poor due to late diagnosis, cancer recurrence, and drug resistance. Epigenetic research, particularly in microRNAs, has introduced a new avenue for cancer prevention and treatment. MicroRNAs, including miR-137, play a vital role in tumor development by regulating various cellular processes. MiR-137 has garnered attention for its tumor-suppressive properties, with studies showing its potential in inhibiting cancer progression. In lung cancer, miR-137 is of particular interest, with numerous reports exploring its role and mechanisms. A comprehensive review is necessary to consolidate current evidence. This review highlights recent studies on miR-137 in lung cancer, covering cell proliferation, migration, apoptosis, drug resistance, and therapy, emphasizing its potential as a biomarker and therapeutic target for lung cancer treatment and prognosis.